Faramerz Dabhoiwala: The Origins of Sex. A History of the First Sexual Revolution - Hayward, Vicky (Petits Propos Culinaires, 2012)
Faramerz Dabhoiwala: The Origins of Sex. A History of the First Sexual Revolution: Allen Lane, 2012, 484 pp., hardback, £25.00.